Exploring manual testing problems of regression testing for i-Care Prime (ICP) system / Elliyana Maton - Maton, Elliyana (2015)
The goal of automation is to ensure that testing phase can give more benefits than current process of manual testing. Often software tester lack time required to fully test the delivered software product within the time period assigned to them. The issues usually cause the software delivery date to slide when issues in the implementation stage of a project development happen. As a way to expertise intense test deadlines, software tester often required further sources as well as to operate extended need to add a long time to the test team for outcome. The solution to this matter is to deliver testers using a test automation platform to facilitate improvement associated with automated test solutions. Test automation shows an important part in testing activity as it delivers better utilization of resources and also can save time. Software systems are very sensitive and complex in their data usage. This creates testing a very essential stage in their life cycle as it supports guaranteeing the quality of the system. Test automation can perform an essential part in decreasing overall time of testing activity by expending the best resources. As a solution to encounter the manual testing issues during regression testing, researcher has proposed one solution which is by propose a framework of test automation. The framework is called Software Test Automation Framework (STAF). In this IT project, some problems of manual testing were exposed. The outcome was shown STAF should be suggested to the organization since have a lot of advantages between others automation framework. For this IT project, it only focuses on regression testing. This research contribution may help stakeholder in improving the software testing system which is in i-Care Prime order management system. For the future works, this research project can be extended by conducting an experimental research or simulation testing and implement the proposed of automation framework to i-Care Prime System.